Aportes filosóficos para una agenda de mujer y construcción de paz en Colombia (2021)
The peace agreement concluded between the Colombian government and the FARC in 2016 has been seen not only as the end of the armed conflict, but also as the possibility of imagining and building an inclusive, fair and participatory society. It has been argued that the peace agreements are the shortest route to achieve the objectives of the State and comply with what is stipulated in its narrative as part of a social pact that leads to peaceful coexistence. However, a detailed and critical look at the descriptive and therefore practical framework of the agreements from a feminist perspective focused on difference, reveals an intentional sense of exclusion and marginalization of women that reproduces the theoretical frameworks of a feminism focused on equality and equity. Luce Irigaray's philosophical thinking allows fracturing and decentralizing the masculine logic in the Western philosophical tradition and opens the way for difference as a concept that recreates and reimagines the public and political space as a possibility for inclusion that strengthens citizenship as a right and sole guarantor of reconciliation in Colombian society.